Differentiation of strains in Mycobacterium tuberculosis complex by DNA sequence polymorphisms, including rapid identification of M. bovis BCG. - Frothingham, R (1995)
The Mycobacterium tuberculosis complex includes M. tuberculosis, M. bovis, M. microti, and M. africanum. Seven strains of the M. tuberculosis complex were sequenced in a region of about 300 bp which contains multiple 15-bp tandem repeats and which is part of a 1,551-bp open reading frame. Four distinct sequences were obtained, each defining a sequevar. A sequevar includes the strain or strains with a given sequence. The type strain M. tuberculosis TMC 102 (H37Rv) was designated sequevar MED-G. When compared to MED-G, sequevar LONG had an insertion of one 15-bp tandem repeat and sequevar SHORT had a deletion of one tandem repeat. Sequevar MED-C had a G-->C substitution, coding for the conservative change Ser-->Thr. BanI cuts only sequevar MED-C at the site of the substitution. PCR-restriction enzyme analysis was used to determine the sequevars of 92 M. tuberculosis complex strains. All 23 M. bovis BCG strains belonged to sequevar MED-C. The M. africanum type strain was sequevar SHORT. The remaining 68 strains of M. tuberculosis, M. bovis (not BCG), and M. microti were sequevars LONG (3 strains) or MED-G (65 strains). PCR-restriction enzyme analysis was applied to reference strains and clinical isolates with a worldwide distribution. This method provides rapid, sensitive, and specific identification of the important vaccine strain M. bovis BCG.